ANALISIS NILAI PENDIDIKAN PADA BUKU CERITA RAKYAT GUA PUTERI DALAM PEMBENTUKAN KARAKTER SISWA KELAS V SD N 129 OKU (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is: how is the implementation of the role of the folktale Gua Puteri in shaping the character of Grade V students at SDN 129 OKU? This research aims to determine how character formation, particularly the development of a sense of responsibility, is built among fifth-grade students at SD Negeri 129 Ogan Komering Ulu, South Sumatra. The study employed a qualitative descriptive method. Data collection techniques included observation, interviews, and documentation. Based on the results, this research discusses the analysis of students’ understanding of responsibility at the elementary school level using the Gua Puteri folktale book as a learning medium. With a total of 20 students, it was concluded that the level of responsibility in this school is relatively good: 4 students (20%) showed a moderate level of responsibility, while 16 students (80%) demonstrated good responsibility. Overall, the majority of students (80%) showed a strong sense of responsibility, indicating the success of the applied learning approach. However, 20% of the students still require additional attention and guidance to further enhance their sense of responsibility.